An ideal biomaterial: Ti-based bone repair material with dual-response antibacterial system and sustained drug release - Zhang, Wentao; Guo, Zhaoyang; He, Zhongyuan; Zhou, Hang; Liu, Hang; Peng, Xinliang; Yang, Xingyu; Zhong, Ru; Huang, Wen; Chu, Lei; Deng, Zhongliang (Frontiers in Bioengineering and Biotechnology, 2025)
Bone infection is a disease with high treatment cost, long period and high disability rate in orthopedics. The development of antibacterial implant materials in vivo can alleviate the pain of patients and social burden. How to make the antibacterial substances in the implant materials release regularly as needed is a key technical breakthrough that antibacterial bone repair implants have been trying to optimize. It has been proved that metal silver ions sputtering can form higher specific surface area on the surface of implanted materials, and can produce electron biological effect to realize in situ sterilization. Antibacterial peptide crosslinked with hyaluronic acid can be hydrolyzed by hyaluronidase during bacterial infection, thus killing free bacteria, producing immune regulation. At present, it is planned to use titanium dioxide nanotubes to construct a double-layer nanotube structure, fill osteogenic drugs into the nanotubes by vacuum-assisted physical adsorption, and sputter deposit metal silver ions on the surface of the nanotubes. The outer layer of the material is prepared by covalent grafting of antibacterial peptides and hyaluronic acid to prepare a layer-by-layer assembly technology shell to prepare a bone implant scaffold material with dual sterilization response systems of electronic biological antibacterial response and enzymatic hydrolysis antibacterial response.